PENDAMPINGAN PERSIAPAN OLIMPIADE SAINS NASIONAL MATEMATIKA SMA TARAKANITA MAGELANG: - Purwadi, Joko; Haryono, Nugroho Agus; Santosa, Gunawan; Jong, Jek Siang (Servirisma, 2024)
Tarakanita Senior High School (SMA) Magelang is one of the private high schools in Magelang, Central Java, which was established in 1984. The problem faced by Tarakanita Senior High School is the lack of teaching staff who can train students to prepare themselves to take part in the 2024 OSN in mathematics. Community service activities aim to help Tarakanita Senior High School students prepare themselves for the OSN Mathematics. The mentoring was attended by 8 students in grades 10 and 11 who were approved by the school to take part in the OSN Mathematics. The method of implementing the activity includes: technical coordination of activities with the vice principal and mathematics teacher, mentoring in preparation for the OSN Mathematics in the form of completing and discussing practice questions, and evaluation with teachers and students of Tarakanita Senior High School Magelang. The series of activities were carried out in November 2023 - April 2024. Evaluation of the success of the activity was carried out at the end of the mentoring for 5 students who actively participated in the activity until the end and 2 mentoring teachers using Gform. The results showed a value of 4.75 (teachers) and 4.58 (students) on a scale of 1 (very bad) to 5 (very good). These results indicate that the implementation of community service has been very good. These results are also reinforced by verbal input from teachers at the end of the activity who expect similar activities to be carried out again in 2025.